Experimental study on using smart material to generate guided wave for structural health monitoring of pipe structures - Shi, Miao. (2011)
In Structural Health Monitoring (SHM), there is a rising interest in using ultrasonic guided wave for Non-Destructive Evaluation (NDE) of the existing structures, especially in hollow cylindrical structures, since pipelines are widely used today in the industry like oil and gas where piping system is important for processing and distribution of the products. Many researchers have contributed to this area in investigation of the pipe system for existence of the crack and crack properties like location, direction, shape and size. Most of them probe into the cracks in the circumferential direction, which is relatively sensitive to the guided waves, while leaving the cracks in the longitudinal direction less explored because of the difficulty in longitudinal crack detection due to lacking sensitivity towards guided waves. However, it is more critical to the safety of the structures.